Critical reflection and dialogical learning design: moving MOOCs beyond unidirectional transmission of content - Mathiesen, Kim Haagen; Nedergaard, Mathias Helbo; Nørgård, Rikke Toft (Tidsskriftet Læring og Medier (LOM), 2016)
Distance education and e-learning has been around for some time now. The ubiquitous development of the internet (Sharples, 2007) has however made way for the emergence of new educational formats such as the much talked-about Massive Open Online Courses (MOOCs). Within MOOCs users have access to educational literature and tasks at all times, which allow users to fit the course into their own pace, place and Personal Learning Environment (Attwell 2007). Today MOOCs has spread across the globe, and in Denmark we now see institutions such as Aarhus University developing a new course with roots in the MOOC format, however without the ‘Massive’ part (Aarhus University, 2016). Over a 5 week period we conducted a netnographic (Kozinet, 2015) mixed methods research of the MOOC Blended Learning Essentials (https://www.futurelearn.com/courses/blended-learning-gettingstarted/2). Contrary to the acclaimed potentials of MOOCs, our research showed a pronounced lack of dialogue and a high degree of what Freire (1996) calls “the banking concept of education,” entailing a high amount of one-way knowledge transmission (Hoem, 2006). To circumvent these tendencies, the paper presents a case analysis and design framework for moving MOOCs beyond “the banking concept of education” and towards dialogue in ways that support critical thinking; a high-level cognitive skill essential to higher education (Laurillard, 2012).